EFEK PENAMBAHAN KITOSAN TERHADAP KARAKTERISTIK FISIKA KIMIA BIOPLASTIK PATI BATANG KELAPA SAWIT - Muhammad Nur Alam; Taqwin Halid; Ilmiati Illing (Universitas Negeri Makassar, 2018)
A research has been conducted to investigate the effect of chitosan addition on water uptake and biodegradation properties of bioplastics. Bioplastic was synthesized from starch of palm stem using direct mixing method with chitosan addition at concentration of 2%, 4%, 6%. The average water uptake of 22.46 % with the lowest water uptake was found to be 14.6 % by the addition of 6% chitosan. The highest biodegradation was found to be 76.8 % by the addition of 4 % chitosan within 15 days of burial in soil. In general, the greater the concentration of chitosan leads to greater bioplastic biodegradation rate.